Assessment of the 18-month permanence of onlay tip cartilage grafts following rhinoplasty. Issue 4 (September 2013) - Persichetti, Paolo; Simone, Pierfranco; Carusi, Carlo
Abstract Augmentation rhinoplasty requires addition of materials of various natures to reshape the nasal pyramid. Onlay tip grafts are single or multilayered grafts placed horizontally over the alar domes. The aim of the present study was to assess the 18-month permanence of onlay septal cartilage grafts. Twenty-eight patients underwent rhinoplasty with onlay tip cartilage graft, between June 2008 and November 2008 at the Campus Bio-Medico University in Rome, Italy. They were reviewed and photographed 6 months and 18 months postoperatively. Comparison of 6-month and 18-month postoperative pictures was performed with Adobe Photoshop CS. Measurements on pictures were taken with AutoCAD. Comparison of photographs showed no visible difference in nasal tip projection. Comparison of the measurements of tip projection showed a mean reduction of 0.06 mm (0.19%). Considerable stability of nasal tip projection after rhinoplasty with onlay tip grafts was observed postoperatively. Comparison of standardised digital photographs is a valid procedure to assess contour alterations of various anatomical structures after plastic surgery.